Neuroticism related differences in the functional neuroanatomical correlates of multitasking. An fMRI study. (2nd December 2016) - Szameitat, Andre J.; Saylik, Rahmi; Parton, Andrew
Graphical abstract: Highlights: High neurotics show higher behavioural multitasking costs than low neurotics. High neurotics show less dual-task specific brain activation than low neurotics. Affected brain areas are lateral- and medial-prefrontal cortices. Abstract: It is known that neuroticism impairs cognitive performance mostly in difficult tasks, but not so much in easier tasks. One pervasive situation of this type is multitasking, in which the combination of two simple tasks creates a highly demanding dual-task, and consequently high neurotics show higher dual-task costs than low neurotics. However, the functional neuroanatomical correlates of these additional performance impairments in high neurotics are unknown. To test for this, we assessed brain activity by means of functional magnetic resonance imaging (fMRI) in 17 low and 15 high neurotics while they were performing a demanding dual-task and the less demanding component tasks as single-tasks. Behavioural results showed that performance (response times and error rates) was lower in the dual-task than in the single-tasks (dual-task costs), and that these dual-task costs were significantly higher in high neurotics. Imaging data showed that high neurotics showed less dual-task specific activation in lateral (mainly middle frontal gyrus) and medial prefrontal cortices. We conclude that high levels of neuroticism impair behavioural performance in demanding tasks, and that this impairment is accompanied by reduced activation of the task-associated brain areas.